Business Penetration in the Development of e-Government Concepts: Challenges of Managing Cloud-Based Website Computing Systems - Dian Suluh Kusuma Dewi; Jusuf Harsono; Desriyanti Desriyanti; Dwiana Binti Yulianti; Arif Zainuddin (Khazanah Sosial, 2024)
In the digital era, e-government initiatives have revolutionised how governments interact with businesses and citizens. This study aims to explore the integration of business processes into e-government models through the implementation of cloud computing-based systems, with a specific focus on the tourism sector in Ponorogo Regency. Using a qualitative methodology that includes documentation review, in-depth interviews, and Focus Group Discussions (FGD), the study identifies key challenges in managing the dolanngebel.com website. The findings highlight significant issues in transparency, participation, and collaboration among government entities, business stakeholders, and the public. These challenges are attributed to organisational inefficiencies, limited human resources, financial constraints, and regulatory hurdles. The study concludes that addressing these issues could improve administrative efficiency, stakeholder engagement, and public trust in e-government services. This research offers original insights into the practical challenges and opportunities of integrating e-government and business models, particularly in the tourism industry, and provides actionable recommendations for policymakers and practitioners.